US-China relations after 9/11 : the impact of the attacks on mutual relations up to 2012 - Šachová, Lucie; Garlick, Jeremy; Veselá, Zuzana; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2024)
This thesis analyzes the dynamics of U.S.-China relations within the framework of complex interdependence. It focuses on the flow of the bilateral relationship in the period after the Tiananmen Square massacre and the development that followed the terrorist attacks of September 11, 2001. The primary aim is to prove that complex interdependence can clarify the balance of cooperation and competition between these two powers. The analysis is divided into two main periods – the post-Tiananmen, and the post-9/11 eras. The post-Tiananmen period emphasizes the shift of U.S.-China relations toward strategic cooperation. Following that, the post-9/11 era focuses not only on the direct aftermath of the attacks, which started a realignment in mutual relations but also on the ongoing development of these relations up to 2012. This included economic, security, as well as diplomatic engagement. Specifically, the thesis analyzes the roles of multiple channels of interaction, the absence of a hierarchy among issues, and the limited use of military force – three key principles of the complex interdependence theory. This is done mainly by examining the changes in strategies and policies, that illustrate the theory’s importance. The results show that the post-9/11 era was characterized by increased economic and security cooperation. Even though the strategic rivalry persisted, the attacks became an incentive for both countries to prioritize economic stability and cooperative security measures.
Vedoucí práce: Jeremy Alan Garlick
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: mezinárodní studia a diplomacie [obor bakal. práce]; bakalářské práce; bachelor's theses